Sustainable Performance Model and Strategy: A Conceptual Framework - Arifin, Firmansyah; Wiryono, Sudarso Kaderi; Damayanti, Sylviana Maya; Yudoko, Gatot (International Journal of Entrepreneurship and Sustainability Studies, 2023)
This study is driven by the conditions of the energy sector, particularly the "oil field service industry" which serves as the main pillar of this sector. The significant oil price drop and the need for cost-cutting among oil and gas producers shows the vulnerabilities in this sector, necessitating improvement. Generally, industries that support key commodities must exhibit strong operational performance that intricately intertwines with the corporate strategy, mitigating potential obstacles, challenges, and business risks in order to achieve sustainable performance. Thus, this research aims to investigate how to develop a sustainable performance model for the industry in helping the industries the current and future business challenges. A systematic literature review was undertaken, encompassing prior studies on sustainable business, performance, and risk management strategies. This study investigates the dynamic interaction between three primary constructs: (1) context-business sustainability, (2) content-performance management, and (3) process-strategy formulation. Finally, gaps in the existing literature were identified and several future research directions were proposed.